Administrative act appeal within the administrative procedure: comparative legal analysis - O. O. Markova (Bulletin of Kharkiv National University of Internal Affairs)
A comparative legal analysis of one of the stages of administrative procedure i.e. the stage of appeal against an administrative act has been carried out. The attention is focused on the study of the provisions of the FRG Law “On Administrative Procedure”, the Code of Administrative Procedure of Poland and the Law of Ukraine “On Administrative Procedure” regarding appealing against the results of administrative procedure. An analysis of the peculiarities of the mechanism for appealing against an administrative act within the framework of administrative procedure in Poland and Germany has been carried out, and a comparison has been made with the provisions of the Law of Ukraine “On Administrative Procedure”, and proposals have been provided for improving the provisions of the law which has not yet entered into force. It has been proved that the Law of Ukraine “On Administrative Procedure” should clarify the provisions on the subject of complaint consideration, given the lack of criteria to be taken into account when selecting the subject of complaint consideration. The Law provides for an alternative composition of the body which is authorised to consider complaints: 1) a higher-level administrative body, unless another entity is provided for by law; 2) a board for reviewing complaints.